Deficiency in phytoalexin production causes enhanced susceptibility of Arabidopsis thaliana to the fungus Alternaria brassicicola - Thomma, B.P.H.J; Nelissen, I; Eggermont, K; Broekaert, W.F (The Plant journal : for cell and molecular biology, 1999)
The phytoalexin-deficient Arabidopsis mutant pad3-1, which is affected in the production of the indole-type phytoalexin camalexin, has previously been shown not to display altered susceptibility to either the bacterium Pseudomonas syringae (Glazebrook and Ausubel, 1994; Proc. Natl. Acad. Sci. USA, 91: 8955-8959) or the biotrophic fungi Peronospora parasitica (Glazebrook et al., 1997; Genetics, 146: 381-392) and Erysiphe orontii (Reuber et al., 1998; Plant J. 16: 473-485). We now show that this mutant is markedly more susceptible than its wild-type parental line to infection by the necrotrophic fungus Alternaria brassicicola, but not to Botrytis cinerea. A strong camalexin response was elicited in wild-type plants inoculated with either Alternaria brassicicola or Botrytis cinerea, whereas no camalexin could be detected in pad3-1 challenged with these fungi. Hence, PAD3 appears to be a key determinant in resistance to at least A. brassicicola. The induction of salicylate-dependent and jasmonate/ethylene-dependent defense genes was not reduced in Alternaria-challenged pad3-1 plants compared to similarly treated wild-type plants. Camalexin production could not be triggered by exogenous application of either salicylate, ethylene or jasmonate and was not, or not strongly, reduced in mutants with defects in perception of these defense-related signal molecules. Camalexin-production appears to be controlled by a pathway that exhibits little crosstalk with salicylate-, ethylene- and jasmonate-dependent signalling events.